Field Studies on the Initial Mortality of Lac Insect Kerria lacca Kerr. in Relation to Host Plants - Bhagat, M. L. (Indian Forester, 1988)
Mortality during crawler stage of Indian lac insect was studied over three years on six lac crops of rangeeni strain in Institute plantation on three different lac hosts. The average mortality percentage was 41.20 to 60.20 on Palas; 30.49 to 48.84 on Ber and 29.65 to 52.98 on Bhalia. The probable causes are not only the climatic factors but also the nature of the twigs for the settlement suitability and struggle between to have wider scope for existance in crawling stage with the ultimate result of mortality due to unavailability of proper place to get nourishment for continuing tbe race.